Larger and More Prominent Graphic Health Warnings on Plain-Packaged Tobacco Products and Avoidant Responses in Current Smokers: a Qualitative Study - Hardcastle, Sarah; Chan, Derwin; Caudwell, Kim; Sultan, S.; Cranwell, J.; Chatzisarantis, N.; Hagger, Martin (Springer New York LLC, 2015)
Background: The introduction of tobacco plain packaging legislation in Australia meant that all tobacco products were to be sold in plain dark-brown packaging with 75 % front-of-pack graphic health warnings and standardised font type and size for brand name and product variant. The change in the size and prominence of the warnings has been proposed as a reason for behaviour change in smokers in terms of increased intentions to quit and quit attempts. Purpose: The current research examined attitudes and beliefs of cigarette smokers toward the increased size and prominence of the warnings and effects on their behaviour. Method: Participants (N = 160) completed open-ended responses to questions on beliefs, attitudes and responses to plain packaging. Responses were subjected to inductive thematic content analysis for key themes. Results: Four themes emerged from the analysis: emotional response to packaging, scepticism of health warnings, warnings and cessation behaviour, and avoidant coping behaviours. Participants reported increased negative emotional responses to the packaging and made specific reference to the graphic health warnings. Some participants attempted to discredit the messages. Others reported increased intentions to quit or quitting attempts. There were pervasive reports of avoidant responses including covering or hiding the warnings. Conclusion: Consistent with theories of illness perceptions and coping, current findings indicate that the larger, prominent graphic health warnings on plain-packaged tobacco products had pervasive effects on threat perceptions and subsequent behavioural responses. While some of the reported responses were adaptive (e.g. attempts to quit), others were maladaptive (e.g. avoiding the warnings).